Analysis of Phishing Attack Trends, Impacts and Prevention Methods: Literature Study - Fauzan Prasetyo Eka Putra; Ubaidi; Achmad Zulfikri; Goffal Arifin; Ilhamsyah, Revi Mario (Yayasan Cita Cendekiawan Al Khwarizmi, 2024)
Phishing is a growing form of cybercrime that poses a serious threat to information security in the digital world. This article aims to analyze the latest trends in phishing attacks and evaluate effective prevention methods. Using data from cybersecurity reports, case studies, and academic literature, this research identifies the latest phishing techniques such as spear phishing, whaling, and smishing that are increasingly sophisticated and difficult to detect. The analysis showed that while anti-phishing technologies such as email filters, two-factor authentication (2FA), and encryption have undergone significant developments, user awareness and education remain key factors in preventing phishing attacks. Additionally, strict policies and procedures at the organizational level also play an important role in reducing risk. The case studies presented in this article demonstrate the successful implementation of various prevention methods in several organizations, although challenges in terms of technology adoption and user training remain. For example, spear phishing and whaling have been effectively countered by tailored training programs and advanced threat detection systems. The article concludes by providing practical recommendations to increase user awareness and strengthen organizational policies to protect against phishing attacks. It also includes foresight to illustrate the possible evolution of phishing attacks, emphasizing the need for continuous innovation in cyber defense strategies. This comprehensive approach underscores the importance of a multi-layered defense system that combines technological solutions with human vigilance to effectively combat the ever-evolving threat of phishing.